Frontispiece: Magnetically Encoded Luminescent Composite Nanoparticles through Layer‐by‐Layer Self‐Assembly. Issue 45 (3rd November 2014) - Song, Erqun; Han, Weiye; Xu, Hongyan; Jiang, Yunfei; Cheng, Dan; Song, Yang; Swihart, Mark T.
<x xml:space="preserve">Abstract</x> Analyte Detection A set of magnetically encoded luminescent composite nanoparticles with distinguishable magnetic susceptibilities and good fluorescence properties were developed through a layer‐by‐layer self‐assembly strategy based on electrostatic interactions. The as‐prepared nanocomposites can be seen as bait to capture multi‐component targets. This nanocomposite‐based assay is time saving and cost efficient, and has potential applications in many areas including bio‐ and chemical research, environmental monitoring, and food safety control. For more information, see the Full Paper by E. Song et al. on page 14642 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>